2008
DOI: 10.3136/fstr.14.431
|View full text |Cite
|
Sign up to set email alerts
|

Increased Volume of Kasutera Cake (Japanese Sponge Cake) by Dry Heating of Wheat Flour

Abstract: A soft wheat flour, Tokutakaragasa (protein 9.69 %), was dry-heated at 120℃ for 10, 20, 30, 60, and 120 minutes, and baked into Kasutera cakes (Japanese sponge cakes). The volume of Kasutera cake increased with duration of dry heating. Also, the stability of foam in Kasutera cake batter increased with the dry-heating time of wheat flour. The mixograph profile of dry-heated wheat flour also suggests the hydrophobicity of wheat flour. Thus, the results suggest that the hydrophobicity of the dry-heated wheat flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 5 publications
0
18
0
3
Order By: Relevance
“…Hanamoto and Bean (1979) patented a method for producing heat treated flour, where the temperature was maintained at 71°C for 4-5 days. Nakamura et al (2008) observed an increase in the volume of Kasutera cake by dry heating of wheat flour at 120°C for 30 min.…”
Section: Introductionmentioning
confidence: 95%
“…Hanamoto and Bean (1979) patented a method for producing heat treated flour, where the temperature was maintained at 71°C for 4-5 days. Nakamura et al (2008) observed an increase in the volume of Kasutera cake by dry heating of wheat flour at 120°C for 30 min.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, a stronger dough or more stable foam can be produced that can tolerate a higher sugar content. Hence, it is suitable for cake butter or biscuit production (Chesterton, Wilson, Sadd, & Moggridge, 2015;Li, Cui, & Kakuda, 2006;Nakamura, Koshikawa, & Seguchi, 2008). It has also been reported that dry heat has an impact on the viscosity properties of flours due to structural changes of gluten molecules.…”
Section: Introductionmentioning
confidence: 97%
“…Heat-treated wheat flours are used in many products such as cakes, biscuits, coatings, sauces, baby foods, and thickeners (Neill, Ala'a, & Magee, 2012). Heat treatment of the flours was found as an alternative treatment to chlorine gas treatment, which increases flour water holding capacity and decreases gluten elasticity to produce baked goods with greater volume, finer texture, and finer grain (Johnson, Hoseney, & Ghaisi, 1980;Nakamura, Koshikawa, & Seguchi, 2008;Ozawa & Seguchi, 2006;Yamamoto, Worthington, Ng, & Finney, 1994). The high temperature and prolonged heat treatment methods as a replacement for chlorination were patented by Russo and Doe (1970) and Hanamoto and Bean (1979).…”
Section: Introductionmentioning
confidence: 99%